2015
DOI: 10.3892/ol.2015.3181
|View full text |Cite
|
Sign up to set email alerts
|

Mature brain-derived neurotrophic factor and its receptor TrkB are upregulated in human glioma tissues

Abstract: Abstract. There are two forms of brain-derived neurotrophic factor (BDNF), precursor of BDNF (proBDNF) and mature BDNF, which each exert opposing effects through two different transmembrane receptor signaling systems, consisting of p75 neurotrophin receptor (p75NTR) and tyrosine receptor kinase B (TrkB). Previous studies have demonstrated that proBDNF promotes cell death and inhibits the growth and migration of C6 glioma cells through p75NTR in vitro, while mature BDNF has opposite effects on C6 glioma cells. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 25 publications
2
12
0
Order By: Relevance
“…It has been reported that mature BDNF and its receptor, TrkB, are upregulated in human glioma tissues ( 19 ); however, its specific mechanism of action has not been clearly explained. Thus, the present study also measured the expression of TrkB in the aforementioned cell lines.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that mature BDNF and its receptor, TrkB, are upregulated in human glioma tissues ( 19 ); however, its specific mechanism of action has not been clearly explained. Thus, the present study also measured the expression of TrkB in the aforementioned cell lines.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, BDNF-AS was demonstrated to be reversely associated with BDNF and downregulated expressed in RB, NSCLC, and CC 12,39,40 . Xiong et al found that mature BDNF induces glioma cells in vitro 41 . However, little is known about the expression or functions of BDNF-AS in human glioma.…”
Section: Discussionmentioning
confidence: 99%
“…This is emphasized by the negative prognostic effect of VAV3 and NOS2 expression in grade IV astrocytoma and for SPC24 in liver tumours [ 40 ]. Similarly, decreased NTRK2 expression in high compared to low grade astrocytoma [ 41 ], decreased ST3GAL6 expression in liver tumours [ 42 ], and increased AKR1C3 expression in 1q19p co-deleted glioma compared to other glioma subtypes [ 43 ] support a low-malignant function, although other studies on NTRK2 [ 44 , 45 ], AKR1C3 [ 46 , 47 ], and ST3GAL6 [ 48 ] are inconsistent.…”
Section: Discussionmentioning
confidence: 99%